Wound healing and photodynamic potential of Adiantum capillus-veneris L. (Pteridaceae): an evaluation of the cellular effects and molecular insights - Mou, Linru; Jalil, Banaz; Scotti, Francesca; Lane, Majella E.; Fiebich, Bernd L.; Sun, Lu; Maake, Caroline; Heinrich, Michael (Frontiers in Pharmacology, 2026)
IntroductionChronic and infected wounds represent a persistent global health burden. Medicinal plants offer a promising source of wound-healing agents due to their multitarget activities, long history of traditional use, and accessibility. Adiantum capillus-veneris L. (ACV), traditionally used to treat a range of ailments, such as respiratory, urinary, and skin disorders, was investigated for its in vitro wound-healing potential following methanol extraction.MethodsWe evaluated the effects of methanol extracts of ACV (ACVM) on cell proliferation, migration and antioxidative capacity in human keratinocytes (HaCaT), and anti-inflammatory activity in RAW 264.7 cells. We also explored its combination with visible light phototherapy.ResultsChemical profiling via HPTLC analysis, UV/Vis spectrophotometry and HPLC analysis, together confirmed that ACVM contained more metabolites than other extracts, yielding five visible-light absorption peaks and identifying rutin and chlorogenic acid as major metabolites. At ≤100 μg/mL, ACVM was non-toxic to HaCaT cells in the absence of visible light. However, phototoxicity was evident at 200 μg/mL. ACVM (50 μg/mL) significantly promoted HaCaT migration, with a further enhancement upon exposure to light. ACVM also suppressed H2O2-induced ROS generation in a dose-dependent manner (≤50 μg/mL), while light exerted a bidirectional modulatory effect. Additionally, ACVM markedly inhibited LPS-induced secretion of CXCL2, CCL2, CXCL10, TNF-α, and IL-6 in RAW 264.7 macrophages, with effects evident at concentrations as low as 0.1 μg/mL.DiscussionThese findings suggest that ACVM, particularly in combination with light-assisted therapy, shows promise for accelerating wound healing.